REPRESENTATION OF JAVANESE LEADERSHIP IN SERAT SAPTASTHA - Afiliasi Ilafi; Bani Sudardi; Supana Supana (Universitas Sebelas Maret, 2017)
Serat Saptastha is one of the ancient manuscripts stored in the library at Sonobudoyo Museum Yogyakarta. Serat Saptastha tells about the events of the lengser keprabon experienced by Hamengku Buwana VII and the transition of power from Hamengku Buwana VII to Hamengku Buwana VIII. The event of lengser keprabon and the power transfer which is considered quite short of its preparation becomes its own history for Kasultanan Yogyakarta. This study explores about how the image of Hamengku Buwana VII as Java’s leader depicted on the content of the manuscript Saptastha. This research uses qualitative methods and data collection techniques using literature study. The image of Sri Sultan Hamengku Buwana VII becomes exemplary as a leader who is respected and coveted by the people.